UMA ANÁLISE DAS RELAÇÕES DE AMIZADE COMO UM ELEMENTO NORTEADOR DAS COMUNIDADES PRIMITIVAS A PARTIR DE JOÃO 15 - MEDEIROS, JOÃO BATISTA NUNES DE (2020)
The concept of “Friendship” was appropriated by the members of the Joanine community and reformulated beyond the socio-cultural context of the Greco-Roman world where this Christian community was inserted. The narrative of the Vine Parable, the hatred that the community faced by the Jews and the world, at the same time, with the ebullition of internal schisms, made the community to seek for the memory of these sayings of Jesus (John 15:1-25), a mechanism that could confirm his connection and knowledge with the Messiah, as well as, strengthen his internal interpersonal relationships. The figure of the vine and its branches represented the unity that the Joanine community claimed to have with the Messiah, as well as demonstrating the connection between the Father and the Son, between the master and his disciples. In the matter of the relationship between master and his disciples, this metaphor also served to reinforce the type of communion that existed between Jesus and his disciples, who were promoted to be his friends. The concept of friend was a counterpoint to the condition of a slave, which served to show that in the Joanine community the belonging people were not mere executors of orders, they enjoyed the privilege of knowing their Lord’s will. The friendship paradigm was the element that the Joanine community chose to guide the building of the relationships of its belongings and its historical journey as an alternative community in the socio-cultural context of the Greco-Roman world in which it was inserted